1996
DOI: 10.1016/s0896-8446(96)90043-1
|View full text |Cite
|
Sign up to set email alerts
|

Corrosive effects of supercritical carbon dioxide and cosolvents on metals

Abstract: With the eventual phase-out of chlorofluorocarbons, and restrictive regulations concerning the use of cleaning solvents such as hydrochlorofluorocarbons, and other volatile organic compounds, it is essential to seek new, environmentally acceptable cleaning processes. In the DOE Complex and in industry, an environmentally sound process for precision cleaning of machined metal parts is one of the issues that needs to be addressed. At Sandia, we are investigating the use of supercritical carbon dioxide (CO2) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…Two semi-empirical formulas have been introduced to describe the relationship between the Young's modulus and the porosity ɛ, as shown in Eq. (17) and (18) [73]: (18) where E 0 is the Young's modulus of pure FeCO 3 crystal, and b is a tunable parameter. According to Ramachandran et al [73], Eq.…”
Section: The Relationship Between the General Corrosion Rate And The mentioning
confidence: 99%
See 2 more Smart Citations
“…Two semi-empirical formulas have been introduced to describe the relationship between the Young's modulus and the porosity ɛ, as shown in Eq. (17) and (18) [73]: (18) where E 0 is the Young's modulus of pure FeCO 3 crystal, and b is a tunable parameter. According to Ramachandran et al [73], Eq.…”
Section: The Relationship Between the General Corrosion Rate And The mentioning
confidence: 99%
“…Therefore, by combining Eq. (18) with Eq. (20), it can be confirmed that the corrosion rate exhibited a logarithmic relationship with the Young's modulus.…”
Section: The Relationship Between the General Corrosion Rate And The mentioning
confidence: 99%
See 1 more Smart Citation
“…When free water exists in the pipeline, it will be saturated with CO 2 and the corrosion rate will be significant for carbon steel because of the formation of carbonic acid (H 2 CO 3 ). In addition, even though pure, dry CO 2 is not corrosive, there are several studies which provide qualitative evidence for corrosion on carbon steel in water-saturated supercritical CO 2 phase (Russick et al, 1996;Propp et al, 1996;McGrail et al, 2009). Thus, to be able to consider the corrosion risk in such pipelines, quantitative evaluation of corrosion in both CO 2 -saturated water and water-saturated CO 2 phases will be needed.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosive attacks can be observed in water saturated CO 2 environments on carbon steel and some aluminum or copper alloys [14]. An important point to determine the corrosivity of supercritical CO 2 media, concerns the mechanisms of formation of free water.…”
Section: Carbon Dioxidementioning
confidence: 99%